Exploring the synergistic effects of flexible work practices, organizational support, and work-life culture in manufacturing firms in Oman - Al Balushi, Badriya Khoda Bakhsh; Jais, Juraifa (Asian Development Policy Review, 2026)
This study examines how flexible work practices (FWPs) influence job satisfaction in Omani manufacturing SMEs and whether work-life balance culture (WLBC) and perceived organizational support (POS) act as mediators and have a synergistic effect. Data were collected from 100 employees across six organizations. Guided by social exchange theory and organizational support theory, reliability, validity, and the direct, indirect, and interaction effects were tested using partial least squares structural equation modeling (PLS-SEM). The findings reveal that FWPs are positively associated with job satisfaction and significantly enhance both WLBC and POS, which in turn increase satisfaction, with WLBC emerging as a stronger predictor. The results indicate that FWPs generate value primarily through relational and cultural mechanisms rather than through structural change. Employee satisfaction peaks when FWPs are implemented alongside strong organizational support and a culture that promotes work–life balance. The study advances SET and OST by demonstrating the dual mediation and synergistic processes through which structural flexibility affects employee attitudes in a Gulf manufacturing context. It also proposes an integrated HR model that aligns flexibility, support, and culture to improve satisfaction and retention. Policymakers and industry leaders in Oman are encouraged to institutionalize flexible work arrangements and supportive workplace cultures through national HR frameworks and labour policies to enhance employee well-being, engagement, and productivity in the manufacturing sector.